Envelope glycoproteins of Human Immunodeficiency Virus type 1 variants issued from mother-infant pairs display a wide spectrum of biological properties - Suzie Thenin (2018)
Several studies have shown that the early virus population present in HIV-1 infected infants usually is homogeneous when compared to the highly diversified viral population present at delivery in their mothers. We explored the antigenic and functional properties of pseudotyped viruses expressing gp120 encoded by env clones issued from four mother-infant pairs infected by CRF01_AE viruses. We compared their sensitivity to neutralization and to entry inhibitors, their infectivity levels and the Env processing and incorporation levels. We found that both transmitted viruses present in infants and the variants present in their chronically infected mothers display a wide spectrum of biological properties that could not distinguish between them. In contrast, we found that all the transmitted viruses in the infants were more sensitive to neutralization by PG9 and PG16 than the maternal variants, an observation that may have implications for the development of prophylactic strategies to prevent mother-to-child transmission. © 2012 Elsevier Inc.